Quality of life associated with breathlessness in the multinational Burden of Obstructive Lung Disease (BOLD) study - Müller, Alexander (2025)
Publisher Copyright: © 2025 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.